Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1471-2288-13-17
|View full text |Cite
|
Sign up to set email alerts
|

Ascertaining invasive breast cancer cases; the validity of administrative and self-reported data sources in Australia

Abstract: BackgroundStatutory State-based cancer registries are considered the ‘gold standard’ for researchers identifying cancer cases in Australia, but research using self-report or administrative health datasets (e.g. hospital records) may not have linkage to a Cancer Registry and need to identify cases. This study investigated the validity of administrative and self-reported data compared with records in a State-wide Cancer Registry in identifying invasive breast cancer cases.MethodsCases of invasive breast cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…This is the most comprehensive Australian analysis of IBR utilization patterns through a population‐based study. The NSW hospitalization data have been demonstrated to have high sensitivity and specificity in identifying patients with breast cancer when validated against cancer registry data . However, we acknowledge the potential for miscoding within administrative datasets.…”
Section: Discussionmentioning
confidence: 96%
“…This is the most comprehensive Australian analysis of IBR utilization patterns through a population‐based study. The NSW hospitalization data have been demonstrated to have high sensitivity and specificity in identifying patients with breast cancer when validated against cancer registry data . However, we acknowledge the potential for miscoding within administrative datasets.…”
Section: Discussionmentioning
confidence: 96%
“…As the primary treatment of CRC is surgical, the APDC is considered to provide reliable independent data on such diagnoses. Recent studies on CRC and breast cancer have shown that cancer diagnosis can be accurately identified using hospital data 15 , 16 …”
Section: Methodsmentioning
confidence: 99%
“…Various epidemiological [11,26,62] and cancer research [36] studies are based on data containing demographics and diagnosis codes of patients in New South Wales (NSW), Australia. For example, the study of [36] used the data of women over 45 who are associated with certain diagnosis and procedural codes indicating invasive breast cancer. These data were obtained from the NSW Cancer Registry and from several routinely-collected administrative and self-reported health datasets in NSW, and they were analyzed to find out their predictive power in identifying invasive breast cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, their authors recognize the need for algorithms that anonymize both demographics and diagnosis codes, in order to prevent identity disclosure [7] and increase data availability [36]. Also, publishing RT -datasets is important to support analysis tasks, including case count studies [46,54], which require accurately counting the number of patients associated with specific demographics and diagnosis codes, predictive modeling, and query answering [61].…”
Section: Introductionmentioning
confidence: 99%